Coexisting hepatitis A and Salmonella Typhi infections presenting as fever of unknown origin in a 22-year-old male (Indian Journal of Case Reports, 2026)
Coinfections involving Salmonella Typhi and hepatitis A are exceedingly rare but can complicate diagnosis and management, particularly in endemic regions where both pathogens share feco-oral transmission routes. We report the case of a 22-year-old male who presented with a 9-day history of fever, abdominal pain, and vomiting. Initial evaluation confirmed hepatitis A infection; however, persistent fever and headache despite supportive management prompted repeat investigations. Blood cultures subsequently isolated Salmonella Typhi, establishing a dual infection. The patient responded to intravenous meropenem and was discharged on oral cefixime. This case is unique because the coexistence of hepatitis A and typhoid fever mimicked a fever of unknown origin, delaying appropriate treatment. It highlights the need to consider multiple concurrent infections in patients presenting with persistent fever and abdominal symptoms in endemic areas. Comprehensive evaluation, including repeat cultures and liver function tests, is essential for accurate diagnosis and timely management.